2011
DOI: 10.1007/s13193-011-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Oncological Surgery: Our Initial Experience of 164 Cases

Abstract: Minimal access surgery is an accepted modality for benign surgery. Despite the advantages of laparoscopy, its acceptance in oncology is slow. Robotic surgery is an emerging field with rapid acceptance because of the 3-dimensional image, dexterity of instruments and autonomy of camera control. We report here our experience of using the Da Vinci robot for various oncological procedures. We performed 164 oncological surgeries from November 2009 to June 2011. The surgeries performed included thoracic, colorectal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Finally, our overall postoperative complication rate was 8.9 per cent, which is much lower than the 14.4 to 21 per cent complication rates published previously. [5][6][7][8][9][10] A randomized controlled trial comparing robotic versus laparoscopic resection for rectal cancer is presently ongoing with an estimated completion date of June 2018. The primary endpoint of this study is the rate of conversion to open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our overall postoperative complication rate was 8.9 per cent, which is much lower than the 14.4 to 21 per cent complication rates published previously. [5][6][7][8][9][10] A randomized controlled trial comparing robotic versus laparoscopic resection for rectal cancer is presently ongoing with an estimated completion date of June 2018. The primary endpoint of this study is the rate of conversion to open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Currently used in urology, gynecology, chest, head and neck, cardiac, general, and pediatric surgeries, da Vinci robotic surgery is expanding worldwide and will continue to grow in the years to come. [1][2][3] On July 13, 2005, da Vinci robotic surgery was approved by the Korean Ministry of Food and Drug Safety, and it is now being used in many specialties and subspecialties for both inpatients and outpatients in that country. 4,5 Although this robotic surgery system is not available in healthcare facilities worldwide, its use will be expanded because of anticipated improved outcomes.…”
mentioning
confidence: 99%
“…In order to maintain the advantages of minimally invasive approach and to avoid the restriction of laparoscopic surgery, robotic surgery is emerging as a reliable surgical option that can achieve the same results as laparoscopic surgery. In this review, Puntambekar S et al, [14] has reported 164 oncological surgeries, which involved thoracic, colorectal, hepatobiliary, gynaecological and urological systems, which were done robotically by using a three arm da Vinchi robot system from Nov 2009 to June 2011. Among these series, they performed surgeries in 37 patients with colorectal malignancies; anterior resections in 33 patients, right hemicolectomies in three patients and abdominoperineal resection (APR) in one patient robotically.…”
Section: Resultsmentioning
confidence: 99%